The Lazier murder: Prince Edward County, 1884 - Sharpe, Robert J. (University of Toronto Press, 2011)
"In December 1883, Peter Lazier was shot in the heart during a bungled robbery at a Prince Edward County farmhouse. Three local men, pleading innocence from start to finish, were arrested and charged with his murder. Two of them—Joseph Thomset and [George] Lowder—were sentenced to death by a jury of local citizens the following May. Nevertheless, appalled community members believed at least one of them to be innocent—even pleading with the prime minister, John A. Macdonald, to spare them from the gallows. The Lazier Murder explores a community's response to a crime, as well as the realization that it may have contributed to a miscarriage of justice. Robert J. Sharpe reconstructs and contextualizes the case using archival and contemporary newspaper accounts. The Lazier Murder provides an insightful look at the changing pattern in criminal justice in nineteenth-century Canada and the enduring problem of wrongful convictions." – jacket cover summary